Characteristics of employment in the food and beverage departments of hotel in the Greater Manila Area - Elwell, Norma A.; Acasio, Florecita B. (1975)
A descriptive study of the food and beverage departments of 35 hotels in the Greater Manila Area licensed by the Department of Tourism to operate as of September 1974 was conducted from February 9 to April 25, 1975. Information was obtained on: general characteristics of the hotels, by means of questionnaires administered to the hotel managers; personal, educational, and technical background of the persons in-charge of the food and beverage departments, by means of questionnaires completed by the food and beverage managers; and on employment conditions and training of food and beverage employees, through interviews conducted with the personnel managers of the hotels. The hotels were predominantly corporate-owned and managed by a general manager. A twin/double room was the most common type of room available for sale among the hotels. The average rate for a hotel room was USD 16.30 a day. Foreign tourists were the most frequent guests in the higher class hotels; local residents, in the lower class hotels. The main source of hotel income was room sales. Three of the hotels did not have a food and beverage department, four were operated by concessionaires and the rest were operated by the hotels. The person in charge of the food and beverage department was a foreign national in deluxe hotels; a Filipino in the lower class hotels. In comparison, the foreigner was younger, had a higher level of education, had more training in food and beverage, and fewer years of work experience in food and beverage operations than his Filipino counterpart. To attain the position of food and beverage manager, the Filipino started to work in the food and beverage department at a lower level and occupied more positions than did the foreign manager. The bigger and higher class hotels had more food and beverage employees than the smaller and lower class hotels. The ratio of the male to female employees in the food and beverage departments of the hotel studies was 6:1. Overall age range was eight to 69. Highest starting salaries were paid for jobs concerned with overall supervision and management of the food and beverage department; lowest for those concerned with washing the dishes, disposing garbage, and storeroom-keeping. Labor turnover was highest ()29.9 per cent for jobs concerned with greeting and seating customers and lowest (3.1 per cent) for those concerned with mixing and dispensing alcoholic beverage. Training was more commonly given to the food and beverage employees in the higher class than those in the lower class hotels. Training needs were primarily in the areas of food preparation and service. Cooks and waiters were the food and beverage employees in greatest need of training. The study revealed the lack of a uniform system of classifying job titles in the food and beverage departments of the hotels studied and the absence of a standardized salary scale for food and beverage employees. The need for adequate and well-planned training programs for food and beverage employees is supported by findings of the study.
Mimeographed.
Thesis (M.S.F.N.)--University of the Philippines, Diliman.
Keywords: Labor supply -- Philippines; Hotels, taverns, etc. -- Philippines -- Greater Manila Area